Effects of pH on Lignin and Cellulose Degradation by Streptomyces viridosporus - Pometto, Anthony L. (1986)
Lignocellulose degradation by Streptomyces viridosporus results in the oxidative depolymerization of lignin and the production of a water-soluble lignin polymer, acid-precipitable polymeric lignin (APPL). The effects of the culture pH on lignin and cellulose metabolism and APPL production by S. viridosporus are reported. Dry, ground, hot-water-extracted corn (Zea mays) lignocellulose was autoclaved in 1-liter reagent bottles (5 g per bottle) and inoculated with 50-ml volumes of S. viridosporus cells suspended in buffers of specific pH (pH 6.0 to 9.2 at 0.4 pH unit intervals). Four replicates of inoculated cultures and of uninoculated controls at each pH were incubated as solid-state fermentations at 37°C. After 6 weeks of incubation the percent loss of lignocellulose, lignin, and carbohydrate and the amount of APPL produced were determined for each replicate. Optimal lignocellulose degradation, as shown by substrate weight loss, was observed in the pH range of 8.4 to 8.8. Only minor differences were seen in the Klason lignin, carbohydrate, protein, and ash contents of the APPLS produced by cultures at each pH. The effects of pH on the degradation of a spruce (Picea pungens) [(14)C-lignin]lignocellulose and a Douglas fir (Pseudotsuga menziesii) [(14)C-glucan]-lignocellulose were also determined at pH values between 6.5 and 9.5 (0.5 pH unit intervals). The incubations were carried out for 3 weeks at 37°C with bubbler-tube cultures. The percentage of initial (14)C recovered as (14)CO(2), (14)C-labeled water-soluble products, and [(14)C]APPL was then determined. The mineralization of lignin and cellulose to CO(2) was optimal at pHs 6.5 and 7.0, respectively. However, the optimum for lignin and cellulose solubilization was pH 8.5, which correlated with the pH 8.5 optimum for APPL production. Overall, the data show that, whereas lignin mineralization is optimal at neutral to slightly acidic pHs, lignocellulose degradation with lignin solubilization and APPL production is promoted by alkaline pHs. These findings indicate that lignin-solubilizing actinomycetes may play an important role in the metabolism of lignin in neutral to alkaline soils in which ligninolytic fungi are not highly competitive.